Formulation and Evaluation of Liposome Moringa Oleifera Seed Oil (Moringa oleifera L.) as Anti-aging - Hartini, Putri Tri; Sumaiyah; Hasibuan, Poppy Anjelisa Zaitun (International Journal of Science, Technology & Management, 2022)
Moringa oil is a natural vegetable oil obtained from the juice of the ripe kernels of the Moringa tree (Moringa oleifera L). Moringa seeds have an oil content of up to 40%, and have antioxidant activity with vitamin E content reaching 51% but have low stability. The purpose of this study was to find the best formulation as an anti-aging on liposome delivery system with a ratio of phosphatidylcholine soy lechitin and cholesterol. The method used is thin layer hydration (Thin Film Hydration). The results of the observation on the best formula are the 6th formula on organoleptic examination which is milky yellow in color, has a distinctive smell of lecithin and cholesterol and is in the form of a thick suspension, with a pH of 6.0, particle size 83.98nm using a particle size analyzer and entrapment efficiency of 96.8 % using a UV-Vis spectrophotometer.